Pengaruh Partisipasi Penetapan Tujuan Terhadap Goal Commitment Dengan Procedural Fairness Dan Interpersonal Trust Sebagai Variabel Pemediasi - Yulia Isfani; Ria Nelly Sari; Al Azhar L (Fakultas Ekonomi dan Bisnis, Universitas Tarumanagara, 2017)
This study aimed to examine (1) the direct effect of goal-setting participation on goal commitment, (2) indirect effect of goal-setting participation on goal commitment with procedural fairness and interpersonal trust as intervening variables. The data for this study was collected by sending a questionnaire via email using the Google Forms. 411 questionnaire are send to middle manager who work of manufacturing companies listed on Indonesia Stock Exchange, and 74 responses are returned and due to incomplete data nine questionnaire were dropped. The hypothesis were tested by using Partial Least Square (PLS)2.0 M3. Seven out of eight hypotheses were accepted. Result of this study proved that (1) goal-setting participation has no significant effect on goal commitment; (2) no direct effect of goal-setting participation on goal commitment; (3) goal-setting participation has indirect effect toward goal commitment through procedural fairness and interpersonal trust as intervening variables.